TEACHING MADURA LOCAL CONTENT LITERACY ON PRESERVICE SCIENCE TEACHER USING LWIS MODEL - Mochammad Yasir; Ana Yuniasti Retno Wulandari (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2020)
Several previous studies have shown that students have difficulty integrating ethnoscience into science learning. Students are more likely to be introduced to the basic concepts of ethnoscience without involving how to integrate ethnoscience into science learning. The impact is that students’ scientific literacy is low. This is what underlies researchers to apply the Local Wisdom Integrated Science (LWIS) learning model by using local Madurese content to train students’ scientific literacy. The aim of this study was to evaluate differences in student scientific literacy after implementing the LWIS learning model in ethnoscience learning with local Madurese content. The method used was pre-experimental study with one group pretest-posttest design. When the study was carried out in the even semester of the 2019/2020 academic year by taking 22 students via purposive sampling technique as a sample of all students in class 6A of science education, Trunojoyo University, Madura. Analysis of data using descriptive statistics and paired sample t test. The results showed that there were different in the scientific literacy of the students using the LWIS learning model before and after studying ethnoscience with local Madurese material. The entire LWIS syntax helps train students' scientific literacy by including self-awareness of the importance of local Madurese content as a learning context. Ethnoscience can be integrated into science learning through the STEAM approach. The contribution of STEAM to the LWIS learning model and self-awareness is very significant in developing ethnoscience learning for local Madurese content from elementary, middle, and tertiary level.